Bioremediation of micropollutants using living and non-living algae - Current perspectives and challenges. (1st January 2022) - Ratnasari, Anisa; Syafiuddin, Achmad; Zaidi, Nur Syamimi; Hong Kueh, Ahmad Beng; Hadibarata, Tony; Prastyo, Dedy Dwi; Ravikumar, Rajagounder; Sathishkumar, Palanivel
Abstract: The emergence and continual accumulation of industrial micropollutants such as dyes, heavy metals, organic matters, and pharmaceutical active compounds (PhACs) in the ecosystem pose an alarming hazard to human health and the general wellbeing of global flora and fauna. To offer eco-friendly solutions, living and non-living algae have lately been identified and broadly practiced as promising agents in the bioremediation of micropollutants. The approach is promoted by recent findings seeing better removal performance, higher efficiency, surface area, and binding affinity of algae in various remediation events compared to bacteria and fungi. To give a proper and significant insight into this technology, this paper comprehensively reviews its current applications, removal mechanisms, comparative efficacies, as well as future outlooks and recommendations. In conducting the review, the secondary data of micropollutants removal have been gathered from numerous sources, from which their removal performances are analyzed and presented in terms of strengths, weaknesses, opportunities, and threats (SWOT), to specifically examine their suitability for selected micropollutants remediation. Based on kinetic, isotherm, thermodynamic, and SWOT analysis, non-living algae are generally more suitable for dyes and heavy metals removal, meanwhile living algae are appropriate for removal of organic matters and PhACs. Moreover, parametric effects on micropollutants removal are evaluated, highlighting that pH is critical for biodegradation activity. For selective pollutants, living and non-living algae show recommendable prospects as agents for the efficient cleaning of industrial wastewaters while awaiting further supporting discoveries in encouraging technology assurance and extensive applications.